The Transformation of the TNI Navy Hospital to a Public Service Agency in the Context of Validating the TNI Navy Health Organization: Literature Review - Setiadi, Tiya; MR Hutagalung, Indriani; Faisol, Ahmad (Yayasan Adra Karima Hubbi, 2026)
Background. Public sector reforms in Indonesia are driving government hospitals toward the Public Service Agency (BLU) model to enhance flexibility and service quality. As a key provider for military personnel and the national system, the Indonesian Navy Hospital (RSAL) is part of this significant management shift. Purpose. This study aims to analyze the transformation process of RSAL into a BLU institution and explore its implications for the validation of the Navy’s health organization. Method. The research utilizes a Systematic Literature Review (SLR) following the PRISMA approach, analyzing academic publications, government regulations, and hospital management data. Results. The BLU model improves financial management and operational efficiency. However, challenges remain in governance and human resources, as the rigid military structure often complicates the adoption of the flexible systems required by the BLU model. Conclusion. Successful transformation requires a comprehensive strategy focused on human resource development, policy alignment, and improved organizational governance to bridge the gap between military and BLU systems.